2020
DOI: 10.1016/j.ejso.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Arterial calcification is a risk factor for anastomotic leakage after esophagectomy: A systematic review and meta-analysis

Abstract: Background: Leakage of the esophago-gastrostomy after esophagectomy with gastric tube reconstruction is a serious complication. Anastomotic leakage occurs in up to 20% of patients and a compromised perfusion of the gastric tube is thought to play an important role. This meta-analysis aimed to investigate whether arterial calcification is a risk factor for anastomotic leakage in esophageal surgery. Method: Embase, Medline, PubMed, Cochrane databases and Google scholar databases were systematically searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…One of these factors includes hypovascularization of the gastric conduit which opposes healing of the anastomosis and consequently contributes to leakages. In retrospective analyses of both participating centres of the current study, major calcifications of the aorta and celiac axis have been shown to be an independent risk factor for anastomotic leakage [20,21]. The preoperative identification of patients at risk for anastomotic leakage allows for personalized treatment programs.…”
Section: Discussionmentioning
confidence: 72%
“…One of these factors includes hypovascularization of the gastric conduit which opposes healing of the anastomosis and consequently contributes to leakages. In retrospective analyses of both participating centres of the current study, major calcifications of the aorta and celiac axis have been shown to be an independent risk factor for anastomotic leakage [20,21]. The preoperative identification of patients at risk for anastomotic leakage allows for personalized treatment programs.…”
Section: Discussionmentioning
confidence: 72%
“…This up-to-date literature review adds value to the previously published reviews by Knight et al [ 28 ] and Hoek et al [ 29 ] concerning the impact of arterial calcification in AL after esophagectomy, by including studies evaluating another radiological risk factor for AL, namely celiac trunk stenosis. Given the fact that the arterial supply of the reconstructed GC which will be anastomosed to the esophageal remnant derives invariably from the right gastroepiploic artery [ 25 ], a branch of the celiac trunk, it is rational to assume that stenosis in the celiac trunk may lead to increased rates of GC necrosis and anastomotic leakage following esophagectomy.…”
Section: Discussionmentioning
confidence: 73%
“…A total of 68 potentially relevant articles were identified through an electronic search of bibliographic databases and a manual search of reference lists, of which 34 were directly excluded as duplicates. Of the remaining 34 articles that underwent full-text evaluation, 25 were excluded for the following reasons: 1 case report of 2 patients [ 33 ], 1 systematic review [ 28 ], 1 systematic review and meta-analysis [ 29 ], and 22 articles which were assessed as irrelevant. Finally, 9 original studies fulfilled the inclusion criteria and were further scrutinized [ 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations